(3fNHI GdOgQ aj YLGFH GdHQ hGdHMQs - (3TjN GdQHhI , CHh YHO Gddg eMeO Hf CHj WGdH GdCfUGQj GdUhaj GdOeTbj, TjN GdQHhg (B/ (3TjN MWjf,J (B727 (3g` s ((3ehSi Hf Ydi GdebQi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi Ndb GdSehGJ hGdCQV hLYd GdXdeGJ hGdfhQ hHYO agPG cJGH SejJg fNHI GdOgQ jTJed Ydi GdYde HgjFI GdCQV s
(3BNQgG (B:s
(3hdeG cGf cPdc aMed GdCeGfI hcda GdOjGfI hSei GdMHjH hGdNdjd hGdebQH hGdLdjd fLR GdcJGH hGdMeO ddg QH GdYGdejf s
(3HBNQ GdeNWhW bQGAI SfI (B749 (3hGdhQbI (B87 (3SGbWIs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B170 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B94s
Keywords: (3GdLZQGajG h GdHdOGfs